'Lost Decade' in Translation : What Japan's Crisis could Portend about Recovery from the Great Recession - Tokuoka, Kiichi (IMF Working Papers; Working Paper ;, 2009)
Is the recovery from the global financial crisis now secured? A strikingly similar crisis that stalled Japan's growth miracle two decades ago could provide some clues. This paper explores the parallels and draws potential implications for the current global outlook and policies. Japan's experiences suggest four broad lessons. First, green shoots do not guarantee a recovery, implying a need to be cautious about the outlook. Second, financial fragilities can leave an economy vulnerable to adverse shocks and should be resolved for a durable recovery. Third, well-calibrated macroeconomic stimulus can facilitate this adjustment, but carries increasing costs. And fourth, while judging the best time to exit from policy support is difficult, clear medium-term plans may help.